Awareness of epilepsy among family members of patients undergoing inpatient treatment at the Emergency Department and Women's Department of Nam Dinh Psychiatric Hospital in 2018 (Vietnam Journal of Community Medicine, 2022)
Objectives of the study: To assess the awareness of family members about the disease and how to treat and care for epilepsy patients at home. Subjects and methods: A cross-sectional descriptive study on 43 family members of patients with epilepsy at Nam Dinh Psychiatric Hospital. Results: The patient's family still lacks a lot of knowledge about the disease such as causes and manifestations of the disease; family members' knowledge of handling is not high; The number of family members said that adherence to medication and nutritional care and morale was higher with over 60% and 90% respectively. Conclusion: Care and management of patients with epilepsy in the community is a matter of concern, it is necessary to improve knowledge and attitudes for family members and communities in patient care to improve the quality of life for patients with epilepsy.
Keywords: Epilepsy, family’s knowledge.